Fermentação alcoólica em batelada alimentada empregando Saccharomyces cerevisiae de características floculantes - Guidini, Carla Zanella (2013)
Researches are done with the aim of select yeast strains that plays a differentiated role in the process of alcoholic fermentation, with the purpose of improve the performance in the ethanol production and decrease the productions costs. In this work it was studied the application of Saccharomyces cerevisiae yeasts with flocculent features in fed batch reactor. It was evaluated the fermentative capacity of six strains of flocculent yeasts. The yeast C2/00 was involved in higher productivity and yield in ethanol compared to other yeasts tested. After it was studied the alcoholic fermentation in fed batch reactor using the yeast C2/00. The fermentations were performed at 32°C and initial pH adjusted in 4.5. The process was optimized in sucrose concentration of 170 g/L, cell concentration in the inoculum of 40% (v/v) and filling time of 6 hours, it is obtaining a yield of 92.20% in relation to the theoretical one, productivity of 6.01 g/L.h and residual sucrose of 42.84 g/L in 10.5 hours of fermentative process. It was studied the influence of cells recirculation during the fermentative process and the influence of initial concentration of ethanol and substrate in inoculum on the fed batch process with the aim of improve the productivity and reduce the residual sugar. From of this study it was obtained 92.75% of yield, 9.26 g/L.h of productivity, 2.9 g/L of residual sucrose concentration and the ethanol concentration produced was 83.37 g/L in 9 hours of fermentative process. The inhibition by the substrate and product model to the kinetics of alcoholic fermentation was proposed. The parameters of model were calculated by means of nonlinear adjust to the experimental results of growth of yeast, substrate consumption and formation of product to the batch reactor. The maximum specific speed of growth was 0.103 h-1 with KI and Ks equal to 109.86 and 30.24 g/L, respectively. With the experimental results of fed batch reactor and fed batch with recycle, it can be noted a good fit to the model proposed, resulting in a maximum specific velocity of growth of 0.080 h-1 to the process in fed batch without recycle and 0.182 h-1 to the fed batch process with recycle of fermentative media. The ethanol concentration in which the production of it is completely inhibited (P max) was 110 gethanol /L , approximately 13.92% (v/v). For the result of maximum concentration of product that inhibits fully the microorganisms growth (Pmax) was 12% (v/v), corresponding to 94.8 g/L of ethanol. The specific velocity of sedimentation (SVS) to the yeast C2/00 in pH 5 was 0.240 min-1 and the sedimentation rate of the test beaker was 0.444 cm/min. The alcoholic fermentation, using the flocculent yeast Saccharomyces cerevisiae in fed batch reactor with recycle of fermentative media provided higher productivity and yields when compared to the reported data by literature, in which used batch reactor or fed batch without recycle of fermentative media.